No Employee an Island: Workplace Loneliness and Job Performance - Ozcelik, Hakan; Barsade, Sigal G. (Academy of Management Journal, 2018)
This research investigates the link between workplace loneliness and job performance. Integrating the regulatory loop model of loneliness and the affect theory of social exchange, we develop a model of workplace loneliness. We focus on the central role of affiliation in explaining the loneliness–performance relationship, predicting that despite lonelier employees’ desire to connect with others, being lonelier is associated with lower job performance because of a lack of affiliation at work. Through a time-lagged field study of 672 employees and their 114 supervisors in two organizations, we find support that greater workplace loneliness is related to lower job performance; the mediators of this relationship are lonelier employees’ lower approachability and lesser affective commitment to their organizations. We also examine the moderating roles of the emotional cultures of companionate love and anger, as well as of the loneliness of other coworkers in the work group. Features of this affective affiliative context moderate some of the relationships between loneliness and the mediating variables; we also find support for the full moderated mediation model. This study highlights the importance of recognizing the pernicious power of workplace loneliness over both lonelier employees and their organizations. We offer implications for future research and practice.